MODERN APPROACHES TO CLINICAL AND LABORATORY DIAGNOSTICS OF RHEUMATOID ARTHRITIS EARLY ONSET - D. G. Rekalov; S. Y. Dotsenko; A. V. Kylinich (Zaporožskij Medicinskij Žurnal)
Rheumatoid arthritis (RA) leads not only to a rapid development of disability, but can influence the life of these patients. One-third of patients with rheumatoid arthritis may have signs of disability during the first 3 years of the onset of the disease, while mortality in patients with RA almost two times higher in comparison with the general population.